Optimal secession rules - Massimo Bordignon; Sandro Brusco (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1999)
Should the constitution of a federation allow for peaceful secession? Constitutionally defined secession rules are optimal ex post if the federation breaks down. However, they may be suboptimal ex ante if the member countries receive a benefit from the perceived long-term stability of the federation and constitutionally defined secession rules increase the probability of a break-up. The optimal social contract trades off ex ante benefits and ex post losses, and it may avoid explicit secession rules. If transfers are costly, the trade off is present even if ex post renegotiation is allowed. Finally, we show that under asymmetric information it is more difficult to keep the federation together and that a secession war may occur.
Keywords: 330; Separatismus; Föderalismus; Verfassungsökonomik; Verhandlungstheorie; Asymmetrische Information; Öffentliches Gut; Theorie